Klasifikasi Yuridis Aset Digital dan Urgensi Reformasi Hukum Benda dalam Sistem Hukum Perdata Indonesia - Husni Kurniawati; Monica Belinda Oksavina (UNIB Press, 2026)
The rapid development of the digital economy has given rise to various forms of digital assets such as cryptocurrencies, Non-Fungible Tokens (NFTs), and digital tokens, challenging the structure of Indonesian civil law, which is still based on the colonial legacy of the Civil Code. This study aims to examine two main issues: first, the legal status of digital assets in the Indonesian civil law system from the perspective of property law; and second, how the legal regulation of digital assets in the modern legal system in Indonesia. This study uses a normative legal research method with a statute approach and a conceptual approach. Primary legal materials include the Civil Code, the P2SK Law Number 4 of 2023, POJK Number 27 of 2024, and the UNIDROIT Principles on Digital Assets and Private Law (2023). The results show that doctrinally, digital assets can be categorized as intangible objects (onlichamelijke zaken) based on the open construction of Article 499 of the Civil Code, although without explicit normative recognition. Ownership of digital assets is realized through control of private keys, which is functionally equivalent to the concept of possession in the Indonesian Civil Code, while the transfer of rights occurs through a leveraging mechanism based on on-chain transactions. On the regulatory side, there is a serious legal vacuum: existing regulations are sectoral and lack synergy, consumer protection is inadequate, and cross-border jurisdiction issues remain unresolved. This study concludes that Indonesia requires a three-layer legal reform: updating Book II of the Indonesian Civil Code to recognize digital assets as a separate category of objects, drafting a specific integrated digital asset law, and adapting smart contract regulations within the national contract law system, with reference to the European Union's MiCA and the UNIDROIT Principles 2023 as international comparative guidelines.